The Black experience in design identity, expression & reflection - Berry, Anne H. 1976-; Collie, Kareem; Laker, Penina Acayo; Noel, Lesley-Ann; Rittner, Jennifer; Walters, Kelly ca. 20. Jh (Allworth Press, 2022)
"The Black Experience in Design, an anthology centering a range of perspectives, spotlights teaching practices, research stories, and conversations from a Black/African diasporic lens. Through the voices represented, this text exemplifies the inherently collaborative and multidisciplinary nature of design, providing access to ideas and topics for a variety of audiences, meeting people as they are and wherever they are in their knowledge about design"-Page 4 of cover
Keywords: African American artists / Social conditions; Graphic artists / Social conditions; African American aesthetics; African American arts; African diaspora; Graphic arts / United States; Graphic arts; Design / United States; Design; Artistes noirs américains / Conditions sociales; Esthétique noire américaine; Arts noirs américains; Africains / Pays étrangers; Arts graphiques / États-Unis; Arts graphiques; Design / États-Unis; United States; Essay; essays; Essays; Essais; Aufsatzsammlung